Enhancing French curriculum: workshop for new course development at UiTM Shah Alarm / Seng Hui Zanne, Nik Nur Nadhirah Zakaria and Mohd Hanafiah Abu Bakar - Seng, Hui Zanne; Zakaria, Nik Nur Nadhirah; Abu Bakar, Mohd Hanafiah (Academy of Language Studies, 2025)
From the 18th to the 22nd of November 2024, the French Language Unit of the Academy of Language Studies (APB) held a new course document workshop at APB. Universiti Teknologi MARA (UiTM) Shah Alam. This face-to-face workshop involves all French language lecturers from UiTM Selangor Branch Shah Alam Campus, a French language lecturer from UiTM Terengganu Branch Dungun Campus and two French language lecturers from UiTM Penang Branch Permatang Pauh Campus.